Valorization of an Old Variety of Triticum aestivum: A Study of Its Suitability for Breadmaking Focusing on Sensory and Nutritional Quality - Alessandro Bianchi; Francesca Venturi; Angela Zinnai; Isabella Taglieri; Basma Najar; Monica Macaluso; Giorgio Merlani; Luciana Gabriella Angelini; Silvia Tavarini; Clarissa Clemente; Chiara Sanmartin (Foods, 2023)
“Avanzi 3-Grano 23” (G23) is an old variety of Triticum aestivum from the mountain areas of Lunigiana (north Tuscany, Italy), where traditional farming communities have contributed to its success and on-farm conservation. G23 flour, traditionally used for typical food products, is characterized by particular nutritional and sensory traits but has technological properties which limit its suitability for breadmaking. The aim of this work was to evaluate how to promote the use of G23 through the optimization of bread formulation by leveraging both flour blending and the leavening system. During the preliminary test, three different mixes of G23 flour and a strong flour (C) were tested in terms of their leavening power as a function of leavening agent (baker’s yeast or sourdough). The selected M2 flour, composed of G23:C (1:1 w/w), was used for further breadmaking trials and 100% C flour was utilized as a control. The sourdough bread obtained with the M2 flour (SB-M2) showed an improved sensory profile compared with the related control (SB-C). Furthermore, SB-M2 exhibited the best aromatic (high content in aldehydes, pyrazines and carboxylic acids) and phytochemical profile (total polyphenols and flavonoids content and antioxidant activity). In contrast, the use of baker’s yeast, although optimal from the point of view of breadmaking, did not result in the same levels of aromatic complexity because it tends to standardize the product without valorizing the sensory and nutritional qualities of the flour. In conclusion, in the experimental conditions adopted, this old wheat variety appears to be suitable for the production of sourdough bakery products.